The role of serum procalcitonin in establishing the diagnosis and prognosis of pleural infection. Issue 1 (December 2017) - Dixon, Giles; Lama-Lopez, Adriana; Bintcliffe, Oliver; Morley, Anna; Hooper, Clare; Maskell, Nick
Abstract Background Bacterial pleural infection requires prompt identification to enable appropriate investigation and treatment. In contrast to commonly used biomarkers such as C-reactive protein (CRP) and white cell count (WCC), which can be raised due to non-infective inflammatory processes, procalcitonin (PCT) has been proposed as a specific biomarker of bacterial infection. The utility of PCT in this role is yet to be validated in a large prospective trial. This study aimed to identify whether serum PCT is superior to CRP and WCC in establishing the diagnosis of bacterial pleural infection. Methods Consecutive patients presenting to a tertiary pleural service between 2008 and 2013 were recruited to a well-established pleural disease study. Consent was obtained to store pleural fluid and relevant clinical information. Serum CRP, WCC and PCT were measured. A diagnosis was agreed upon by two independent consultants after a minimum of 12 months. The study was performed and reported according to the STARD reporting guidelines. Results 80/425 patients enrolled in the trial had a unilateral pleural effusion secondary to infection. 10/80 (12.5%) patients had positive pleural fluid microbiology. Investigations for viral causes of effusion were not performed. ROC curve analysis of 425 adult patients with unilateral undiagnosed pleural effusions showed no statistically significant difference in the diagnostic utility of PCT (AUC 0.77), WCC (AUC 0.77) or CRP (AUC 0.85) for the identification of bacterial pleural infection. Serum procalcitonin >0.085 μg/l has a sensitivity, specificity, negative predictive value and positive predictive value of 0.69, 0.80, 0.46 and 0.91 respectively for the identification of pleural infection. The diagnostic utility of procalcitonin was not affected by prior antibiotic use (p  = 0.80). Conclusions The study presents evidence that serum procalcitonin is not superior to CRP and WCC for the diagnosis of bacterial pleural infection. The study suggests routine procalcitonin testing in all patients with unilateral pleural effusion is not beneficial however further investigation may identify specific patient subsets that may benefit. Trial registration The trial was registered with the UK Clinical Research Network (UKCRN ID 8960 ). The trial was approved by the South West Regional Ethics Committee (Ethical approval number 08/H0102/11).